Invigorasi Benih dengan Berbagai Zat Pengatur Tumbuh (Zpt) Terhadap Cabai Keriting (Capsicum annum L) - Dava Swa Sambayu; Muharam Muharam; Elia azizah (Peneliti.net, 2021)
This study aims to get a combination of seed sources and which ZPT provides the best viability, vigor seed, and growth of curly chili seedlings (Capsinum annuum L.). The research was conducted from July to November 2020 in gauze houses and residential areas. The research method used is the experimental method of Randomized Design Group (RDG) with 10 combination treatments namely A (new seed harvest + Control), B (new seed harvest + Onion Extract), C (new seed harvest + Bean sprout extract), D (new seed harvest + Young coconut water), E (new seed harvest + Giberelin), F (Expired seed + Control), G (Expired seed + Red Onion Extract), H (Expired seed + Bean extract) , I (Expired Seed + Young Coconut Water), J (Expired Seed + Giberelin). Each treatment is repeated 3 times so that there are 30 experimental units. The effect of the treatment is tested with a variety analysis and if the F test at the level of 5% the results show significant then to know the best treatment followed by dmrt test (Duncan Multiple Range Test) level 5%. The results of the study in phase 1 showed that the combination of seed source and ZPT had a real effect on germination power parameters, vigor index, growth speed.